Economic Development of Jayapura Regency, Papua Province Based on the Potential of Leading Regional Economic Sectors - Timisela, Stephany Inagama; Sanggrangbano, Agustina; Antoh, Agustina Ester; Duwiri, Daniel Nafta (Jurnal Penelitian Ekonomi dan Bisnis, 2025)
This study aims to identify and analyze the economic sectors that are the leading sectors and potential sectors of the region that can be developed to improve the regional economy of Jayapura Regency, using time series data from 2013-2021 which were analyzed using Economic Sector Contribution Analysis, Growth Ratio Model Analysis, Location Quotient Analysis, Shift-Share Analysis, Klassen Typology Analysis of GRDP Sector Approach, Klassen Typology Analysis of Leading Sector Approach, and Overlay Model Analysis of Jayapura Regency. The results of the study show that Jayapura Regency has 14 leading economic sectors that play an important role in driving economic activities and economic development of Jayapura Regency, one of which is the primary sector, namely the Agriculture, Forestry, and Fisheries sector. For this reason, in the future, mapping of the sub-sectors that are the leading primary sectors can be carried out so that the development of superior regional products can be carried out, one of which is through the establishment of the Jayapura Regency Regional-Owned Enterprise engaged in the fields of Agriculture, Forestry, and Fisheries.